SPEECH DEVELOPMENT IN LINGUISTIC RESEARCH - Abdurashidova, Nilufar (Журнал иностранных языков и лингвистики, 2023)
Our article offers an analysis of the speech and the term from different angles dedicated to the origin of the term. In addition, the author examines the studies of scholars and language schools to understand this concept more deeply.